2014
DOI: 10.1007/s11430-014-4975-4
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous palynology and paleoclimate change: Evidence from the SK1 (South) core, Songliao Basin, NE China

Abstract: Cretaceous climate was warmer than today. The Songliao Basin contains one of the most important Late Cretaceous non-marine deposits in China for the research of the paleoenvironment and paleoclimate. This research is based on core samples from the SK1(S) borehole. The strata sampled are the upper part of the Quantou Formation to member 2 of the Nenjiang Formation, where spores, pollen, dinoflagellates, and other microfossils are abundantly preserved. Based on analysis of the spores and pollen fossils from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 25 publications
(27 reference statements)
3
12
1
Order By: Relevance
“…The global paleoclimate was suggested to hot during this period [2]. Based on the core of SK1(s) from the Songliao Basin, a detailed study of spore and pollen suggested a relatively warm and wet climate during Late Turonian [5], which is consistent with our results. Dur-…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The global paleoclimate was suggested to hot during this period [2]. Based on the core of SK1(s) from the Songliao Basin, a detailed study of spore and pollen suggested a relatively warm and wet climate during Late Turonian [5], which is consistent with our results. Dur-…”
Section: Resultssupporting
confidence: 90%
“…Open Journal of Geology still not well understood. The Well-preserved Cretaceous lacustrine deposits in this basin provide a unique opportunity to study terrestrial paleoenvironments and paleoclimate during the Late Cretaceous [4] [5]. Here, the microfossils from the Late Turonian Qingshankou Formation of the Songliao Basin were used to study the paleoenvironments and paleoclimate of East Asia.…”
mentioning
confidence: 99%
“…4), which may be related to massive freshwater input in a short time (unpublished hydrogen isotopic data) (Zhao et al, 2014). Relative to the C 28 and C 29 4a-methyl steranes, the C 30 4a-methyl sterane is clearly enriched in 13 C, which may reflect the variation in water salinity.…”
mentioning
confidence: 91%
“…Thus, the massive black shale sedimentation during the Cretaceous period is also associated with the high productivity of the ocean rather than the anoxic event itself. Previous evidence from algae fossils and biomarkers have shown that there was high lacustrine productivity during the depositional period of K 2 n 1 and K 2 n 2 (Yang et al, 1981;Feng et al, 2009;Zhang and Bao, 2009;Xi et al, 2012;Wang et al, 2013;Zhao et al, 2014), but they show obviously different OM abundances. The OM content is high under the anoxic condition in K 2 n 1 , but the OM abundance declines rapidly during K 2 n 2 with its oxic environment, which suggests that even under the condition of high productivity, it still difficult to form a high OM deposit if there is not a good preservation environment for the OM.…”
mentioning
confidence: 97%
“…An increasing number of studies suggest that the formation of a hydrocarbon source rock in K 2 n 1+2 of the SLB relates to the marine transgression (Hou et al, 2000;Xi et al, 2011a;Huang et al, 2013;Hu et al, 2015). While paleontologic data indicates (Gu and Yu, 1999;Sha, 2007;Wan et al, 2013;Ye et al, 2002;Zhao et al, 2014) changes in lake water salinity during the Late Coniacian to early Campanian (Table 1), the exact reason for the formation of the massive hydrocarbon source rock in K 2 n 1 + 2 is still unknown (Li and Pang, 2004). The specific environmental changes that took place within the paleo-lake resulting from seawater incursions during the marine transgression in K 2 n 1 + 2 remain unclear.…”
Section: Mongolocypris Obscura Mongolocypris Tabulatamentioning
confidence: 99%